Bidirectional Management of a Transnasal Intracranial Chopstick Transecting Optic Nerve. Issue 4 (June 2018) - Tsai, Tsung-You; Lee, Li-Ang; Chao, Wei-Chieh; Lee, Yi-Chan
Abstract : Abstract: Herein, the authors report a rare patient with a transnasal intracranial penetration injury caused by a chopstick that resulted in optic nerve transection as well as the removal of the chopstick using a bidirectional approach. A 25-year-old male presented to our emergency department with right blindness and bilateral epistaxis. Preoperative computed tomographic angiography demonstrated a transnasal stick-like foreign body causing a skull base fracture and suspected vascular injury. Due to the shape of the chopstick and the high risk of massive bleeding, an exclusively endoscopic or open craniotomy approach is not suitable for removal. A bidirectional method, including both an open craniotomy and transnasal endoscopy, was used to remove the chopstick. After the operation, there were no further neurologic deficits or complications during the treatment course and follow-up. The bidirectional approach may provide an alternative method to address a foreign body when the patient is not a candidate for an exclusively endoscopic or open craniotomy approach management.